Legal review of the implementation of work safety and health atpt multi nabatimaleo unit, pohuwato district - SULAIMAN, HERLINA (Jurnal Hukum Volkgeist, 2019)
Implementation of Occupational Safety and Health at PT. Multi Nabati Unit Maleo is done by Enviromental Unit, Health and Safety. EHS is a policy applied by PT Multi Nabati Unit Maleo in providing protection for the safety and health of its workers. EHS is a direct handle or the first handle if there is an accident and also work to make preventive efforts to prevent accidents. In addition, the company develops the health and work safety management system (SMK3 & L). The efforts undertaken by PT Multi Nabati To reduce the risk of occupational accidents by applying: Engineering (engineering), Administration (administration) and Labor must use APD (Personal protective equipment).